A conspectus of the genus Pigea (Violaceae) in India - Parappurakkal Thazhe Arunraj; Divya V. Nair; Viswanathamandiram Natarajakaimal Sanjai (Plant Science Today, 2024)
An updated conspectus of the genus Pigea in India is provided based on live and herbarium specimens. We recognize three species, namely P. enneasperma, P. indica and P. travancorica and exclude three species from the National Flora, namely P. vatsavayae ( Hybanthus vatsavayae), P. stellarioides ( H.stellarioides) and P. puberula ( H. puberulus). Detailed notes are provided.